2021
DOI: 10.2807/1560-7917.es.2020.26.1.2002011
|View full text |Cite
|
Sign up to set email alerts
|

Minimal transmission of SARS-CoV-2 from paediatric COVID-19 cases in primary schools, Norway, August to November 2020

Abstract: An intense debate on school closures to control the COVID-19 pandemic is ongoing in Europe. We prospectively examined transmission of SARS-CoV-2 from confirmed paediatric cases in Norwegian primary schools between August and November 2020. All in-school contacts were systematically tested twice during their quarantine period. With preventive measures implemented in schools, we found minimal child-to-child (0.9%, 2/234) and child-to-adult (1.7%, 1/58) transmission, supporting that under 14 year olds are not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 10 publications
(19 reference statements)
10
103
0
2
Order By: Relevance
“…Over 18 weeks, this screening program detected 37 of the 126 total positive tests among students and staff engaged in in-person learning, and in-school transmission was rare. These findings are consistent with data from Australia, the UK, Norway, Germany, and Italy, 7–9,18,19 as well as emerging data from K-12 schools across the US. 10,16,17,20–22 However, rare in-school transmissions did occur associated with breaks in mitigation protocols, consistent with data from Israel, Utah, and Mississippi.…”
Section: Discussionsupporting
confidence: 89%
“…Over 18 weeks, this screening program detected 37 of the 126 total positive tests among students and staff engaged in in-person learning, and in-school transmission was rare. These findings are consistent with data from Australia, the UK, Norway, Germany, and Italy, 7–9,18,19 as well as emerging data from K-12 schools across the US. 10,16,17,20–22 However, rare in-school transmissions did occur associated with breaks in mitigation protocols, consistent with data from Israel, Utah, and Mississippi.…”
Section: Discussionsupporting
confidence: 89%
“…Recent infection surveys using PCR tests,1718 show that around 0.5-1% of children have a positive result, and school closures mean it has not been possible to obtain evidence regarding the spread of the new variant in schools. However, earlier studies, including from Australia, Norway, Switzerland, Italy, and Germany,1920212223 in which all individuals were tested regardless of symptoms found transmission rates to be low, particularly among primary schoolchildren 1920212223. Ecological studies and descriptive studies of viral prevalence within schools show that it reflects community prevalence but is not higher 24…”
Section: Transmissionmentioning
confidence: 91%
“…Even during periods of moderate to high community transmission, in many countries few outbreaks have been observed among children in schools where infection control measures have been implemented. [11][12][13] Although some outbreaks have been reported in educational settings during early 2020 (eg, in Israel 14 and the United States 15 ), full or partial opening of schools in many countries in autumn 2020 has not resulted in increased outbreaks. 11 16-18 Most studies in schools have focused on people with identified SARS-CoV-2 infection and subsequent contact tracing within schools.…”
Section: Introductionmentioning
confidence: 99%